Evidence Based Case Report : Prolonged Screen Time as a Risk Factor for Childhood Obesity - Firdausy, Mutiara Auliya; Mutmainna, Faradila Zatsa; Sunukanto, Jennifer Sahira; Fitri, Fadhilah Yuza (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2024)
Background: The COVID-19 pandemic has affected children's daily activities, including school activities that are forced to be conducted online and thus increasing their total screen time. Along with this increase, there is likewise an increase in the prevalence of childhood obesity as children become less active. However, it is still unclear how prolonged screen time becomes a risk factor for overweight/obesity in children. This paper aims to determine the association between prolonged screen time and overweight/obesity in children. Methods: The articles in this study were selected from four databases (Pubmed, Embase, Cochrane Library, and ScienceDirect) with language limitations (published in English). Each of the included studies was evaluated using Oxford Critical Appraisal Tools. Discussion: There are three articles that are included in this study, two of which are meta-analysis and systematic review, and the other one is a cohort study. The included studies have positive similarities with clinical questions and showed positive associations between prolonged screen time and overweight/obesity in children. Two meta-analysis studies showed positive correlation with each odds ratio are 1,67 (95% CI(1.48,1.88)) and 1,262 (95% CI(1.155,1,379)). Another article showed large increases in TSB (time spent in sedentary behavior) (? 81.3) among overweight students and a modest increase (? 27.4) among obese students compared to normal weight students. Conclusion: Prolonged screen time (>2 hours/day) has a significant relationship with increased BMI leading to overweight or obesity.